Characterisation of ten commercial sorghum genotypes grown under water-limited conditions for bioenergy production in Mediterranean environment - Fracasso, Alessandra; Perego, Alessia; Amaducci, Stefano (Italian Journal of Agronomy, 2017)
The evaluation of commercial hybrids under limited water availability is of primary importance to assess Sorghum bicolor (Moench) as potential multipurpose bioenergy crop in Mediterranean drought prone environments. Ten genotypes were grown during three growing seasons (2010, 2011 and 2012) in open field trials and in pot experiments (2014). Phenological traits, biomass production, fibre content and biomass chemical composition were measured under irrigated and rainfed conditions. Differences in biomass production among the ten genotypes varied across years. In a three-year experiment significant differences were found among the ten genotypes in terms of duration of vegetative growth (P<0.05) and aboveground dry biomass production (P<0.1) in response to irrigated and rainfed conditions. Among the ten genotypes analysed, the hybrid ABF306 stands for its performance in terms of biomass production and chemical composition. In fact, it showed the lowest biomass yield reduction when grown under rainfed conditions, the highest drought tolerance index (=0.9), a Â°Brix value comparable to that of sweet sorghum genotypes (8.8 Â°Brix under rainfed conditions), lignin content that was not statistically influenced by water availability, and a lignin cellulose ratio (0.087) favourable for biogas production. The shoot transpiration efficiency and the total transpiration efficiency recorded at high (Exp1) and low (Exp2) vapour pressure deficit were comparable, and sometimes higher, to that of commercial sorghum hybrids. All these characteristics make ABF306 a suitable candidate for bioenergy production in Mediterranean drought prone environments.